Tonic Neuromuscular Processing Affects Postural Adaptation Differently in Aging and Parkinson's Disease - Wright, W. Geoffrey (Frontiers in Neurology, 2019)
The combination of phasic and tonic neuromuscular processes are involved in the maintenance of normal upright posture. The latter is of particular importance in some pathologies, such as Parkinson’s Disease (PD), which is known by one of its cardinal symptoms, tonic dysfunction (i.e. rigidity). Changes in tonic function may also occur during healthy aging. In this investigation, somatosensory input was manipulated by changing the support surface orientation for prolonged periods of quiet stance (QS). The aim was to shed light on how long-term tonic responses called postural lean after-effects are affected by aging and age-related neuropathology. 41 participants were tested: 19 healthy young (25 yrs), 13 healthy older (59 yrs), and 9 adults with PD (57yrs). Baseline conditions were eyes-closed QS on a stable surface or standing on an unstable, sway-referenced (SR) surface. Four experimental conditions combined two types of toes-up ramp tilt adaptation (120s of toes-up static 7º tilt or sinusoidal 7º±3º tilt) with two types of post-adaptation (120s of QS or SR). Results revealed postural after-effects during post-adaptation QS showing significant anterior COP shift for both young and older adults (p<0.0001), but not PD (p>0.06, n.s.). Compared to young, postural after-effects in older adults showed longer decay constants and did not return to baseline COP within the 120s post-adaptation period (p<0.05). Postural after-effects during SR, which appeared as toes-up surface tilt were highly significant in healthy populations (p=0.001) but not PD. Young adults showed significantly larger dorsiflexion (p<0.01) and faster decay constants than older adults (p<0.05). After-effects in PD were absent in the SR conditions (p>0.1, n.s.). In summary, 1) postural after-effects decayed to baseline when post-tilt surface was stable but returned to toes-up tilt during SR post-adaptation in all groups, 2) postural after-effects differed between healthy age groups, 3) PD showed less adaptation to surface changes. Differences in size and decay of after-effects between healthy and PD groups suggest tonic neuromuscular processes play a role in how adaptable postural control is to changing surface conditions and this is affected by healthy aging and basal ganglia function.